Comparison of the sensory properties of fragrant and non-fragrant rice (Oryza sativa), focusing on the role of the popcorn-like aroma compound 2-acetyl-1-pyrroline. (1st March 2021) - Wei, Xuan; Sun, Qianting; Methven, Lisa; Elmore, J. Stephen
Highlights: 2-Acetyl-1-pyrroline (2-AP) is a key discriminator of fragrant and non-fragrant rice. Trained panel could not discriminate fragrant rice varieties with 2-fold variation in 2-AP. Popcorn-like aroma and flavour of 2-AP could be perceived in non-fragrant rice. The odour perception of 2-acetyl-1-pyrroline fits Stevens' law. Abstract: 2-Acetyl-1-pyrroline (2-AP) has been widely reported as a key contributor to the popcorn-like aroma of fragrant rice ( Oryza sativa ). To gain a greater understanding of its contribution to the aroma in both fragrant and non-fragrant rice, sensory profiling was conducted with a trained panel to examine the sensory properties of six boiled rice samples, three fragrant and three non-fragrant varieties. The intensity of the popcorn note as an orthonasal odour, a retronasal flavour and as an after-effect was significantly higher in fragrant rice than in non-fragrant rice. However, panellists could not differentiate these popcorn attributes between the three different fragrant rice varieties. 2-AP was extracted from the boiled rice samples by headspace solid-phase microextraction and quantified by gas chromatography–mass spectrometry. 2-AP was below the limits of quantitation in non-fragrant varieties; however, gas chromatography–olfactometry of samples indicated the presence of 2-AP in both raw fragrant and non-fragrant rice varieties.